Desenvolvimento de procedimentos de preparo de amostras usando sistemas em fluxo - Marques, Thiago Linhares (Universidade Federal de São Carlos, 2017)
Sample preparation using flow and flow-batch systems were here studied. Initially, it was evaluated a microwave-assisted flow digestion system operated under high pressure and high temperature for sample preparation of solid samples of animal and plant tissues (bovine liver, bovine muscle, shrimp, spinach, tomato and orange leaves) and liquid samples of foods (apple juice, mango juice, whole and partially skimmed milk) for macro and micronutrients determination by ICP OES. The digestion efficiencies of glucose, glycine, phenylalanine and nicotinic acid solutions, which are compounds considered easy, medium, difficult and hard to digest, were 98, 63, 22 and 4%, respectively, in the selected conditions (500 W and 5 mL min-1). The developed microwave-assisted flow digestion system showed similar or better digestion efficiencies than other systems described in the literature. Most concentrations of elements determined in CRMs of bovine liver (NIST 1577b) and apple leaves (NIST 1515), which were digested with 6 mol L-1 HNO3, were in good agreement with certified values. Best digestion efficiencies of solid samples (ca. 90%) were reached when using a mixture of 6 mol L-1 HNO3 with 0.4 mol L-1 HCl. Using the digestion mixture composed by 3.7 mol L-1 HNO3 plus 0.3 mol L-1 HCl best digestion efficiencies were reached for fruit juices (ca. 77%), while for milk digestion was more effective (ca. 76%) using 10.5 mol L-1 HNO3. Macro and micronutrient concentrations determined in these samples agreed well with the contents determined by microwave-assisted acid digestion on closed vessels according to a paired t test for multiple samples (P = 95%). Alternatively, it was evaluated a flow-batch extraction system for online determination of macro and micronutrients by ICP OES. The best extraction conditions were reached using 50 mg of sample, 4 min of extraction time with 10 mL of 8 and 4 % (V V-1) HCl for plant and animal tissues, respectively. Quantitative extractions of Cu, Mg, Mn, Na and K were reached in 30 s for spinach leaves, while 4 min were needed for Ca, Ba and Sr. Bovine liver required 4 min of extraction time for all these analytes. These extractions conditions were applied for samples of plant and animal tissues and CRMs previously mentioned and the extraction efficiencies ranged from 80 to 117% for most analytes. According to a paired t test at a 95% confidence level there was no significant differences for most elements determined by flow-batch extraction and microwave-assisted digestion in closed vessels. The exception was Fe in all evaluated conditions for all samples since it is strongly linked to the sample matrix. Both flow systems were promising for sample preparation, but they still need to be improved for routine analysis applications. The microwave-assisted flow digestion system was effective for determination of a large number of elements, but it required sophisticated devices. On the other hand, the developed flow-batch extraction system is simple, but it is not applicable for quantitative determination of elements strongly linked to sample matrices.
Development of sample preparation procedures using flow systems
Keywords: Digestão em fluxo; Extração em fluxo-batelada; ICP OES; Análise multielmentar; Flow digestion; Flow-batch extraction; Multielement analysis; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::INSTRUMENTACAO ANALITICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::METODOS OTICOS DE ANALISE